The Visitor's Hand-Book for Holyhead : Comprising a History of the Town, the Antiquities and Sublime Scenery of the Mountain - Jackson, Thomas, 1798-1873 (Salt Lake City, UT : Project Gutenberg, 2016)
"The Visitor's Hand-Book for Holyhead" by Thomas Jackson is a guidebook detailing the history, scenery, and attractions of the town of Holyhead written in the mid-19th century. The book aims to serve both tourists and locals by providing comprehensive information about significant local historical sites, natural beauties, and other points of interest in the region. The opening of the text sets the stage by describing the background that prompted its creation$1 (Bnamely, the growing interest in Holyhead due to its newly constructed railway and increased visitation from tourists seeking to recuperate from their laborious lives. Jackson shares a vivid portrayal of Holyhead's transformation from a modest fishing village to a thriving port, highlighting the natural wonders, such as the South Stack Lighthouse and the magnificent scenery of the surrounding mountains. He also touches upon ancient history and local customs, suggesting the depth of culture that exists in conjunction with the landscape. Jackson's narration provides not only practical information for visitors but also instills a sense of local pride in Holyhead's rich heritage and natural beauty. (This is an automatically generated summary.)s
Release date is 2016-06-07
Transcribed from the 1853 Smith and Sons edition by David Price
Keywords: Holyhead (Wales) -- Guidebooks